Compressive and diametral tensile strength of glass ionomer cements Resistência à compressão e à tração diametral de cimentos de ionômero de vidro - Eduardo Bresciani; Terezinha de Jesus Esteves Barata; Ticiane Cestari Fagundes; Akimi Adachi; Marina Martins Terrin; Maria Fidela de Lima Navarro (University of São Paulo, 2004)
The aim of this study was to compare, in different periods of time, the compressive and diametral tensile strength of a traditional high viscous glass ionomer cement: Fuji IX (GC Corporation), with two new Brazilian GIC's: Vitro-Molar (DFL) and Bioglass R (Biodinamica), all indicated for the Atraumatic Restorative Treatment (ART) technique. Fifteen disk specimens (6.0mm diameter x 3.0mm height) for the diametral tensile strength (DTS) test and fifteen cylindrical specimens (6.0mm diameter x 12.0mm height) for the compressive strength (CS) test were made of each GIC. Specimens were stored in deionized water at 37º C and 100% of humidity in a stove until testing. Five specimens of each GIC were submitted to CS and DTS test in each period, namely 1 hour, 24 hours and 7 days. The specimens were tested in a testing machine (Emic) at a crosshead speed of 1.0mm/min for CS and 0.5mm/min for the DTS test until failure occurred. The data were submitted to two-way ANOVA and Tukey tests (alpha=0.05). The mean CS values ranged from 42.03 to 155.47MPa and means DTS from 5.54 to 13.72 MPa, with test periods from 1h to 7 days. The CS and DTS tests showed no statistically significant difference between Fuji IX and Vitro Molar, except for CS test at 1-hour period. Bioglass R had lowest mean value for CS of the cements tested. In DTS test Bioglass R presented no statistically significant differences when compared with all others tested GICs at 1-hour period and Bioglass R presented no difference at 24-hour and 7-day periods when compared to Vitro-Molar. Further studies to investigate other physical properties such as fracture toughness and wear resistance, as well as chemical composition and biocompatibility, are now needed to better understand the properties of these new Brazilian GIC's. Comparou-se a Resistência à Compressão (RC) e à Tração Diametral (TD) de um cimento de ionômero de vidro de alta viscosidade [Fuji IX (GC Corporation)] e de dois novos cimentos Brasileiros [Vitro Molar (DFL) e Bioglass R (Biodinamica)], recentemente lançados no mercado, ambos indicados para o Tratamento Restaurador Atraumático (ART), em diferentes períodos de tempo. Foram confeccionados quinze corpos-de-prova com 6,0 mm de diâmetro x 3,0 mm de altura para o teste de TD e quinze com 6,0 mm de diâmetro e 12,0 mm de altura para o teste de RC, para cada ionômero a ser testado. Os corpos-de-prova foram armazenados em recipientes plásticos, com água deionizada, e mantidos em estufa a 37ºC e 100% de umidade, até a realização dos testes. Cinco corpos-de-prova de cada material foram submetidos aos testes de TD e RC em cada período de tempo: 1-hora, 24-horas e 7-dias, em uma máquina de testes universal (EMIC - DL 500) a uma velocidade de 1,0 mm/min para RC e 0,5mm/min para TD. Os dados obtidos foram submetidos aos testes ANOVA a dois critérios e Tukey (á=0,05). Os valores médios de RC e TD variaram de 42,03 a 155.47 MPa e de 5,54 a 13,72 MPa, respectivamente para os períodos analisados. O Fuji IX e o Vitro Molar não apresentaram diferenças em relação aos testes de RC e TD, exceto para RC no período de 1-hora. O Bioglass R apresentou os menores valores de RC dos cimentos testados. Na TD o Bioglass R não apresentou diferença em relação aos outros cimentos testados no período de 1-hora e não foi diferente do Vitro-Molar nos períodos de 24-horas e 7-dias. Mais estudos são necessários para avaliar outras propriedades mecânicas desses novos cimentos de ionômero de vidro brasileiros, tais como: tenacidade e desgaste, bem como composição química e biocompatibilidade.